2018
DOI: 10.1016/j.jebo.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Paying is believing: The effect of costly information on Bayesian updating

Abstract: The supposed irrelevance of historical costs for rational decision making has been the subject of much interest in the economic literature. In this paper we explore whether individual decision making under risk is a¤ected by the cost of information. To do so one must distinguish the e¤ect of cost from self selection by individuals who value information the most. Outside of the laboratory it is A previous version of this paper was circulated under the title "Information at a Cost". y For their useful comments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Thus, the data from the meta-analysis sample points to underinference from a sample size of 1. 26 Among experiments with binomial updating problems and a sample size of 1 that did not meet all the criteria for inclusion in the meta-analysis, nearly all found substantial underinference or slight underinference, 27 with one exception (Robalo and Sayag, 2014). 28 One experiment observed overinference in an experimental condition with asymmetric rates that are close to each other .…”
Section: B Evidence From Simultaneous Samplesmentioning
confidence: 99%
“…Thus, the data from the meta-analysis sample points to underinference from a sample size of 1. 26 Among experiments with binomial updating problems and a sample size of 1 that did not meet all the criteria for inclusion in the meta-analysis, nearly all found substantial underinference or slight underinference, 27 with one exception (Robalo and Sayag, 2014). 28 One experiment observed overinference in an experimental condition with asymmetric rates that are close to each other .…”
Section: B Evidence From Simultaneous Samplesmentioning
confidence: 99%
“…Thus, the data from the meta-analysis sample points to underinference from a sample size of 1. 27 Among experiments with binomial updating problems and a sample size of 1 that did not meet all the criteria for inclusion in the meta-analysis, nearly all found substantial underinference or slight underinference, 28 with one exception (Robalo and Sayag, 2014). 29 One experiment observed overinference in an experimental condition with asymmetric rates that are close to each other .…”
Section: B Evidence From Simultaneous Samplesmentioning
confidence: 99%
“…Ashraf, Berry, and Shapiro (2010), Cohen and Dupas (2010), and (Tadesse & Zewdie, 2019) found no evidence for SCT in their research in African countries in the health sector, possibly because of the different context. On the other hand, Hidalgo, Onofa, Oosterbeek, and Ponce (2013) found the sunk cost effect in the school sector in Ecuador and Robalo and Sayag (2018) found that subjects overweigh costly information relative to free information. A recent study in the Netherlands by Ketel, Linde, Oosterbeek, and Van Der Klaauw (2016) of undergraduate students in HE found no impact of sunk costs on motivation to attend and perform in tuition classes run by a private company in the university.…”
Section: Performance and Retention At Universitiesmentioning
confidence: 99%